Psymberin, a marine-derived natural product, induces cancer cell growth arrest and protein translation inhibition - Dayanidhi, Divya L.; Somarelli, Jason A.; Mantyh, John B.; Rupprecht, Gabrielle; Roghani, Roham Salman; Vincoff, Sophia; Shin, Iljin; Zhao, Yiquan; Kim, So Young; McCall, Shannon; Hong, Jiyong; Hsu, David S. (Frontiers in Medicine, 2022)
Colorectal cancer (CRC) is the third most prevalent form of cancer in the United States and results in over 50,000 deaths per year. Treatments for metastatic CRC are limited, and therefore there is an unmet clinical need for more effective therapies. In our prior work, we coupled high-throughput chemical screens with patient-derived models of cancer to identify new potential therapeutic targets for CRC. However, this pipeline is limited by 1) the use of cell lines that do not appropriately recapitulate the tumor microenvironment, and 2) the use of patient-derived xenografts, which are time-consuming and costly for validation of drug efficacy. To overcome these limitations, we have turned to patient-derived organoids. Organoids are increasingly being accepted as a “standard” preclinical model that recapitulates tumor microenvironment cross-talk in a rapid, cost-effective platform. In the present work, we employed a library of natural products, intermediates, and drug-like compounds for which full synthesis has been demonstrated. Using this compound library, we performed a high-throughput screen on multiple low-passage cancer cell lines to identify potential treatments. The top candidate, psymberin, was further validated, with a focus on CRC cell lines and organoids. Mechanistic and genomics analyses pinpointed protein translation inhibition as a mechanism of action of psymberin. These findings suggest the potential of psymberin as a novel therapy for the treatment of colorectal cancer.